Racial and Ethnic Inequities in Buprenorphine and Methadone Utilization Among Reproductive-Age Women with Opioid Use Disorder: an Analysis of Multi-state Medicaid Claims in the USA - Xu, Kevin Y.; Schiff, Davida M.; Jones, Hendrée E.; Martin, Caitlin E.; Kelly, Jeannie C.; Bierut, Laura J.; Carter, Ebony B.; Grucza, Richard A. (Journal of general internal medicine : JGIM, 2023)
Background Associations between race/ethnicity and medications to treat OUD (MOUD), buprenorphine and methadone, in reproductive-age women have not been thoroughly studied in multi-state samples. Objective To evaluate racial/ethnic variation in buprenorphine and methadone receipt and retention in a multi-state U.S. sample of Medicaid-enrolled, reproductive-age women with opioid use disorder (OUD) at the beginning of OUD treatment. Design Retrospective cohort study. Subjects Reproductive-age (18–45 years) women with OUD, in the Merative™ MarketScan® Multi-State Medicaid Database (2011–2016). Main Measures Differences by race/ethnicity (non-Hispanic White, non-Hispanic Black, Hispanic, “other” race/ethnicity) in the likelihood of receiving buprenorphine and methadone during the start of OUD treatment (yes/no) were estimated using multivariable logistic regression. Differences in time to medication discontinuation (days) by race/ethnicity were evaluated using multivariable Cox regression. Results Of 66,550 reproductive-age Medicaid enrollees with OUD (84.1% non-Hispanic White, 5.9% non-Hispanic Black, 1.0% Hispanic, 5.3% “other”), 15,313 (23.0%) received buprenorphine and 6290 (9.5%) methadone. Non-Hispanic Black enrollees were less likely to receive buprenorphine (adjusted odds ratio, aOR = 0.76 [0.68–0.84]) and more likely to be referred to methadone clinics (aOR = 1.78 [1.60–2.00]) compared to non-Hispanic White participants. Across both buprenorphine and methadone in unadjusted analyses, the median discontinuation time for non-Hispanic Black enrollees was 123 days compared to 132 days and 141 days for non-Hispanic White and Hispanic enrollees respectively ( χ 2 = 10.6; P = .01). In adjusted analyses, non-Hispanic Black enrollees experienced greater discontinuation for buprenorphine and methadone (adjusted hazard ratio, aHR = 1.16 [1.08–1.24] and aHR = 1.16 [1.07–1.30] respectively) compared to non-Hispanic White peers. We did not observe differences in buprenorphine or methadone receipt or retention for Hispanic enrollees compared to the non-Hispanic White enrollees. Conclusions Our data illustrate inequities between non-Hispanic Black and non-Hispanic White Medicaid enrollees with regard to buprenorphine and methadone utilization in the USA, consistent with literature on the racialized origins of methadone and buprenorphine treatment.